Epidemiological pattern of trauma among children 0-9 years in Cameroon. - Odette Dzemo Kibu; Sithombo Maqungo; Georges Nguefack-Tsague; Dickson Shey Nsagha; Nicholas Tendongfor; Fanny Nadia Dissak Delon; Darwin Touko; Elvis Asangbeng Tanue; Rasheedat Oke; Sandra Irene McCoy; Sabrinah Ariane Christie; Catherine Juillard; et al. (PLoS ONE)
Background In low- and middle-income countries, trauma is the leading cause of death among youth and it is also a major cause of disability. Globally, more than 1,600 children and adolescents below the age of 19-years die every day from preventable injuries. Traffic-related injuries, falls, sports-related injuries, assaults, burns, and drownings are the most commonly reported causes of traumatic mortality among children. The mechanism of injury is always diverse in different contexts due to the differences in social determinants of health. Objectives To determine the epidemiological pattern of trauma among children 0-9 years in Cameroon. Methods This is a retrospective analysis of prospectively collected data from the Cameroon Trauma Registry currently running in 10 pilot sites across seven of the ten regions of Cameroon. We retrieved data for all children aged 0-9 years from June 2022 to August 2023. Data was analyzed with respect to the demographics, injury characteristics and outcomes. Results Of the 5,439 patients captured in the trauma registry, 267 (4.9%) were children aged 0-9 years. Over 50% (152/267) of the patients were males with 35% (93/267) from rural settings. The top injury mechanism was road traffic injuries (RTI) [137(52.1%)]. These injuries occurred on the streets [142(53.4%)] during leisure activities [205(78.5%)]. Majority of children [104(39%)] involved in RTI injuries were pedestrians and no prehospital care offered to 216(82.8%) of injured children. A total of 39 (16.9%) were discharged with major disability, 111 (48.1%) had limited ability to move and 5 (2.2%) demised or succumbed to their injuries. There was a significant association between injury activity and gender (P = 0.006). Unlike the females, majority of the males were discharged with major disability [21 (53.8%)]. Conclusion This preliminary analysis highlights the burden of trauma among children aged 0-9 years and its contribution to the proportion of disabled persons in Cameroon. Leisure activities on the streets increased the number of pediatric injuries especially among males. It is therefore imperative to put in place or reinforce environmental interventions to reduce the burden of pediatric injuries.